PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP NILAI PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2020-2024 - Fahmi Fahmi; Sasmita Nabila Syahrir; Surianto Ilham; Iien Rohmatin Nisa (Jurnal Akuntansi Kompetif, 2026)
This study aims to examine the effect of Corporate Social Responsibility (CSR) on firm value in mining companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The mining sector was selected because of its high environmental and social impact, which increases public and regulatory pressure for transparent CSR implementation. A quantitative correlational approach was applied using secondary data obtained from companies’ annual reports and sustainability reports. The sampling technique employed purposive sampling, resulting in 8 mining companies with 40 firm-year observations. CSR was measured using a disclosure index based on the Global Reporting Initiative (GRI) guidelines, covering environmental, social, and economic dimensions. Firm value was proxied by Price to Book Value (PBV), reflecting market assessment of the company’s performance and future prospects. The results of descriptive analysis indicate that CSR disclosure levels among sampled companies are generally high and relatively homogeneous, with an average score close to full disclosure. Meanwhile, firm value shows greater variability across observations. The simple linear regression analysis demonstrates that CSR does not have a statistically significant effect on firm value, as indicated by a significance value of 0.874 (p > 0.05) and a very low coefficient of determination. This finding suggests that limited variation in CSR disclosure reduces its explanatory power in influencing market valuation. Additionally, investors in the Indonesian capital market may place stronger emphasis on financial performance indicators, profitability, and macroeconomic conditions rather than CSR disclosure alone. Therefore, although CSR plays an essential role in maintaining corporate legitimacy and reputation, its direct impact on firm value in the mining sector during the post-pandemic period is not empirically supported.